2015
DOI: 10.20996/1819-6446-2015-11-3-293-296
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nebivolol on Bone Mineral Density in Postmenopausal Women With Mild Hypertension

Abstract: 293Артериальная гипертензия (АГ) и ишемическая бо-лезнь сердца (ИБС) являются наиболее частыми за-болеваниями взрослого населения и характеризуют-ся высокой степенью риска преждевременной смер-ти [1]. По мнению экспертов ВОЗ остеопороз также при-знан одним из наиболее распространенных заболе-ваний, которое наряду с инфарктом миокарда, ин-сультом, онкологическими заболеваниями и внезап-ной смертью занимает ведущее место в структуре за-болеваемости и смертности населения [2]. По мнению экспертов Международного ф… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In conformance with present results, Rodrigues et al reported that propranolol suppresses periodontal bone resorption. In addition, our findings are in harmony with the previous report by Tepoyan et al that nebivolol increases BMD in postmenopausal hypertensive osteoporotic women.…”
Section: Discussionsupporting
confidence: 93%
“…In conformance with present results, Rodrigues et al reported that propranolol suppresses periodontal bone resorption. In addition, our findings are in harmony with the previous report by Tepoyan et al that nebivolol increases BMD in postmenopausal hypertensive osteoporotic women.…”
Section: Discussionsupporting
confidence: 93%